Širjenje obzorij o poučevanju glasbe (University of Maribor Press, 2025)
Broadening Horizons on Teaching Music. In the monograph Broadening Horizons on Teaching Music, students of the Master’s programme in Elementary Education at the Faculty of Education, University of Maribor, explored contemporary findings on music teaching, particularly at the primary school level. This monograph, aimed at teachers and students, provides theoretical insights into numerous key musical concepts and their practical application in pedagogical work. It addresses various aspects of music teaching, the development of musical thinking, the integration of singing and playing, and topics that promote the enhancement of pedagogical skills. Challenges included the appropriate use of digital tools based on artificial intelligence, such as Elicit and ChatGPT, which have transformed traditional research approaches. Despite the advantages of these technologies, students were tasked with ensuring the authenticity and originality of their research, mastering the ethical use of technology, and maintaining academic integrity when citing sources. The monograph concludes with a series of reflective questions to help students and teachers reflect on, refine and plan improvements to their pedagogical practise in primary music teaching.